2005
DOI: 10.1111/j.1468-0262.2005.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Risk in Financial Markets

Abstract: This paper considers a general equilibrium model in which the distinction between uncertainty and risk is formalized by assuming agents have incomplete preferences over state-contingent consumption bundles, as in Bewley (1986). Without completeness, individual decision making depends on a set of probability distributions over the state space. A bundle is preferred to another if and only if it has larger expected utility for all probabilities in this set. When preferences are complete this set is a singleton, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 41 publications
7
117
0
1
Order By: Relevance
“…Other (published) applications of ambiguity averse preferences include Epstein andWang (1994, 1995), who explain …nancial crashes and booms, Mukerji (1998), who explains incompleteness of contracts, Chateauneuf, Dana, and Tallon (2000), who study optimal risk-sharing rules with ambiguity averse agents, Greenberg (2000), who …nds that in a strategic set-up a player may …nd it bene…cial to generate ambiguity about her strategy choice, Mukerji and Tallon (2001), who show how incompleteness of …nancial markets my arise because of ambiguity aversion, Rigotti and Shannon (2005), who characterize equilibria and optima and study how they depend on the degree of ambiguity, Bose, Ozdenoren and Pape (2006), who study auctions under ambiguity, Nishimura and Ozaki (2007), who…”
Section: Applicationsmentioning
confidence: 99%
“…Other (published) applications of ambiguity averse preferences include Epstein andWang (1994, 1995), who explain …nancial crashes and booms, Mukerji (1998), who explains incompleteness of contracts, Chateauneuf, Dana, and Tallon (2000), who study optimal risk-sharing rules with ambiguity averse agents, Greenberg (2000), who …nds that in a strategic set-up a player may …nd it bene…cial to generate ambiguity about her strategy choice, Mukerji and Tallon (2001), who show how incompleteness of …nancial markets my arise because of ambiguity aversion, Rigotti and Shannon (2005), who characterize equilibria and optima and study how they depend on the degree of ambiguity, Bose, Ozdenoren and Pape (2006), who study auctions under ambiguity, Nishimura and Ozaki (2007), who…”
Section: Applicationsmentioning
confidence: 99%
“…Suppose that B-events are unambiguous in the sense that they are stochastically independent of the credal state, while A-events are potentially ambiguous in the sense that they are dependent on the credal state but independent of the B-events. Then p jkji in equation (36) has the factorization p jkji = p jji q k : This is a model-speci…c de…nition of ambiguity that refers to unobservable states of mind, rather than a behavioral de…nition, but it describes a scenario in which the second-order uncertainty model should be expected to produce ambiguity-averse behavior. In particular, it might be expected that a decision maker with these beliefs and aversion to credal uncertainty would be more averse to betting on A-events than B-events in the sense of assigning higher ambiguity premia to A:B-bets than to B:A-bets, analogous to the property of the two-source utility function that was established in Corollary 2.…”
Section: Ambiguity Aversion As Aversion To Second-order Uncertaintymentioning
confidence: 99%
“…A model of preferences that are incomplete due to indeterminacy of probabilities was introduced into microeconomics by Bewley (1986), who referred to it as "Knightian" uncertainty 1 . Its implications for phenomena such as general equilibrium have been elaborated by Rigotti and Shannon (2005) and others. A decision maker with incomplete preferences does not have …xed indi¤erence curves, and she may exhibit indecision or inertia when called upon to make a choice under ambiguous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such incomplete preferences include Bewley's [2] and Rigotti and Shannon [15] incomplete preferences. Under this representation assumption, it is easy to define and characterize the concepts of no-arbitrage prices and no unbounded utility arbitrage.…”
Section: Introductionmentioning
confidence: 99%
“…Agents are assumed not to have enough information to quantify uncertainty by a single probability, hence each agent has a set of priors. Agents are further assumed to have risk averse Bewley's [2] (or Rigotti and Shannon [15] ) incomplete preferences. Under standard conditions on utility indices (strict concavity and increasingness) and sets of priors (convexity and compactness), it is shown that a necessary and su cient for the existence of an individually rational e cient allocation or equilibrium is that the relative interiors of the agents' sets of risk adjusted probabilities intersect or that agents do not engage in mutually compatible trades that have non negative expectations with respect to their risk adjusted probabilities.…”
Section: Introductionmentioning
confidence: 99%